Pengaruh Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Serta Implikasinya Terhadap Produktivitas Karyawan PT. Denso Indonesia Departemen Production Control dan Logistic - Wahyu Murti; Cokro Purwoto (Fakultas Ekonomi Universitas Borobudur, 2021)
The sampling technique used accidental sampling, which is based on the number of 130employees of PT. Denso Indonesia department of production control and logistics, with thenumber of samples obtained as many as 98 respondents. The data analysis technique used in thisstudy is the Path Analysis method and uses an analysis tool, namely SPSS 23.The test results show that the work discipline variable has a positive and significant effectdirectly on employee performance. Work environment has a positive and significant effect directlyon employee performance. Work discipline has a positive and significant effect directly onemployee productivity. The work environment has a positive and significant effect directly onemployee productivity. Employee performance has a positive and significant effect directly onemployee productivity. Work discipline has an indirect and positive effect on work productivitythrough employee performance. And the work environment has a positive and significant indirecteffect on employee productivity through employee performance.Keywords: Work Discipline, Work Environment, Employee Performance, and EmployeeProductivity